2014
DOI: 10.1074/jbc.m113.536201
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Chromodomain-like Insertion of Translation Elongation Factor 3 Compromise Protein Synthesis through Reduced ATPase Activity

Abstract: Background: Eukaryotic translation elongation factor 3 (eEF3) is a ribosome binding ATPase essential for fungal protein synthesis. Results: Mutations in the chromodomain-like insertion in an ATPase domain of eEF3 reduce ATPase activity but not ribosome binding. Conclusion:The chromodomain-like insertion affects the ATPase activity of eEF3 and translation. Significance: The chromodomain-like insertion of eEF3 may be targeted to develop new antifungal compounds.Translation elongation is mediated by ribosomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
(28 reference statements)
2
16
0
1
Order By: Relevance
“…Therefore, we wanted to determine whether a general defect in translation would be enough to cause an increase in eIF2␣ phosphorylation levels. Analysis of other eEF1A as well as eEF2 and eEF3 mutants known to affect translation elongation (29,30) showed that increased eIF2␣ phosphorylation does not result from a general reduction in translation elongation (Fig. 1B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we wanted to determine whether a general defect in translation would be enough to cause an increase in eIF2␣ phosphorylation levels. Analysis of other eEF1A as well as eEF2 and eEF3 mutants known to affect translation elongation (29,30) showed that increased eIF2␣ phosphorylation does not result from a general reduction in translation elongation (Fig. 1B).…”
Section: Discussionmentioning
confidence: 99%
“…1B). To determine whether the phosphorylation effect was due to a general inhibition of translation, we analyzed the level of eIF2␣ phosphorylation in eEF2 and eEF3 mutants with established translation elongation defects (29,30). Neither of the eEF2 and eEF3 mutants gave rise to increased eIF2␣ phosphorylation (Fig.…”
Section: Eef1a-ura3p F308l and S405p Strains Exhibit Increasedmentioning
confidence: 99%
“…The chromodomain interacts through multiple sites with the ribosome. While mutation of ribosome-contacting residues in the chromodomain did not affect ribosome binding, they did impair cell growth, elongation rate, and ribosome-stimulated ATPase activity (Sasikumar and Kinzy 2014). Interestingly, many of the eEF3 mutations isolated in screens based on different eEF3 functions cause inhibition of the ATPase activity, indicating the central role of this activity to eEF3 function on the ribosome.…”
Section: Aa-trna Delivery By Eef1mentioning
confidence: 99%
“…This included eEF3, a fungal specific protein having previously been proposed as a drug target with overexpression in germlings [32] (above). eEF3 is involved in a fungal specific aspect of translation, and mutations in it can deleteriously affect growth and translation [130]. Hence, eEF3 has emerged as a promising diagnostic antigen and drug target.…”
Section: Immunoproteomic Strategies: Considerationsmentioning
confidence: 99%